Comparison of microwave decalcification with conventional decalcification method by using different decalcifying agents - Rehan, Ahmad Danish; Saigal, Sonal; Bhargava, Ankur; Kumar, Uddipan; Thakur, Pragya; Kausar, Tasnim (International Journal of Research in Medical Sciences, 2017)
Background: In routine histopathology, decalcification of teeth is an essential and important step during tissue processing. The present study was attempted to decalcify teeth using microwave method and to compare it with conventional decalcification method. The aim of the study was to compare microwave decalcification with conventional decalcification method with respect to the speed of decalcification, preservation of tissue structure, and efficacy of staining. Methods: In our study, the total sample size used for both routine and microwave decalcification was 30 premolar teeth. The three solutions were diluting nitric acid (5%), formic acid (5%), and EDTA (14%). Results: The results in the present study confirmed the fact that the microwave method using nitric acid was indeed the fastest decalcifying method needing just about 4 days for premolars, compared with routine decalcification. The results also showed that the overall structural details and good staining characteristics were better in teeth decalcified by 5% nitric acid in comparison to EDTA and formic acid in both the methods used. But nitric acid showed good staining details in microwave method in comparison to conventional method. Conclusions: 5% nitric acid by microwave method proved to be the best decalcifying agent as it was fast and gave good structural details and staining characteristics.